A systematic literature review of implementation quality control and assurance in Industries - Riawan, Awinda (JMEL : Journal of Mechanical Engineering Learning, 2025)
Quality management practices are essential for companies seeking a competitive advantage in today's market, with quality control (QC) and quality assurance (QA) playing pivotal roles in ensuring that products and services meet established standards and customer expectations. The integration of these practices with sustainability initiatives has emerged as a critical area of research across various industries, driven by the demand for efficient resource utilization and environmental protection. This paper reviews the significance of QC and QA across these industries, highlighting their impact on operational efficiency, waste reduction, and customer trust. Furthermore, the paper examines the integration of advanced technologies, such as automation and artificial intelligence, in quality management systems, and their potential to improve decision-making and risk management. This review identifies key research gaps and limitations in current studies, emphasizing the need for actionable guidelines and qualitative insights to enhance the implementation of quality management practices. By addressing these gaps, future research can contribute to more effective and sustainable quality management solutions across diverse industries.